Electrical shock injuries: an analysis of voltage, frequency, and contact mode determinants - Gangidi, Suma; Govande, Mukul; McCollum, Kyle; Lee, Raphael C. (Frontiers in Disaster and Emergency Medicine, 2024)
This communication examines the precision of medical terminology commonly used to diagnose and understand the pathogenesis of electrical shock injuries. As everyday technology becomes increasingly reliant on advanced electrical mechanisms that involve more efficient electrical energy transmission modes, waveforms, and frequencies, emergency and trauma physicians will continue to encounter a broader array of electrical injury manifestations. This motivates the following analysis and review of diagnostic terminology related to electrical shocks. The pathogenesis of electrical injury is dependent on the tissue electric field strength, frequency, current duration, and tissues involved. Some traditional diagnostic terms obscure the complexity of this pathogenesis, likely impeding medical management and advances in electrical safety science. Examples include diagnostic terms such as "entry" and "exit" wounds, "arc-flash burns," as well as "high-voltage" and "low-voltage" electrical injuries. This communication includes the scientific rationale for suggested medical terminology changes and will hopefully motivate future refinement.